Effect of Traditional Chinese Medicine decoction cupping combined with wet compress therapy in the treatment of hemiplegia caused by stroke (中药水罐联合溻渍法治疗中风偏瘫临床疗效观察) - YANG Juhang (杨俊行); HU Zhe (胡哲); SU Rong (苏容); WANG Xin (王欣); ZHAO Ning (赵宁) (Association of Integrative Nursing, 2021)
Objective To explore the clinical effect of Traditional Chinese Medicine (TCM)decoction cupping combined with wet compress therapy in the treatment of hemiplegia caused by stroke. Methods Totally 120 patients with hemiplegia caused by stroke were selected. According to TCM nursing interventions provided, they were divided into routine Chinese medicine rehabilitation training group (group A), TCM decoction cupping group (group B) and TCM decoction cupping combined with wet compress therapy group (Group C). The improvement of motor function was evaluated by the simplified Fugl-Meyer Motor Function Assessment Scale (FMA), the recovery of limb muscle strength was evaluated by Lovett's scale before and after treatment, and the improvement of daily living ability were evaluated by Modified Barthel Index (MBI). Patients' satisfaction with TCM nursing treatment was evaluated by self-made questionnaire. Results The symptoms of all patients were significantly relieved after TCM nursing treatment. In comparison between groups, the FMA and MBI scores of patients in group C after treatment were significantly higher than those in groups A and B (t=-3. 871, P＜0. 001; t=-5. 646, P＜0. 001; t=-3. 661, P＜0. 001; t=-2. 131, P=0. 036), while the recovery of muscle strength on the affected side of group C was not statistically different from that in groups A and B (P>0. 05). The patient satisfaction rate was 61. 90%(26/42) in group A, 81. 25%(26/32) in group B and 82. 61%(38/46) in group C. Conclusion TCM decoction cupping combined with wet compress therapy can achieve a sound effect in the treatment of hemiplegia caused by stroke. Additionally, this method is simple, practicable, and with good patient satisfaction, which can be clinically promoted and applied. (目的 探讨中药水罐联合溻渍法治疗中风偏瘫的临床疗效。方法 120例中风偏瘫患者按治疗方式分为A、 B、C3组。A组常规干预, B组在A组基础上实施中药水罐治疗, C组在A组基础上实施中药水罐联合中药溻渍治疗。观察3组患者干预前后偏瘫侧肢体运动功能改善情况、肌力恢复情况以及日常生活能力改善情况, 记录3组护理满意度。结果 干预后, 3组症状均得到缓解, C组患者治疗后的简化版运动功能评定量表(FMA)、改良Barthel指数评分数表(MBI)评分显著高于A、B组(t=-3. 871, P＜0. 001; t=-5. 646, P＜0. 001; t=-3. 661, P＜0. 001; t=-2. 131, P=0. 036), 3组肌力比较无明显差异(P＞0. 05)。A组护理满意度为61. 90%(26/42), B组护理满意度为81. 25%(26/32), C组满意度为82. 61%(38/46)。结论 中药水罐联合中药溻渍治疗中风偏瘫效果显著, 能有效改善患者肢体功能, 提升患者的日常生活自理能力。)